(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2016)
In the past decade, the use of flow cytometry in the clinical haematology laboratory has grown substantially due to the development of smaller, user-friendly, less-expensive instruments and a continuous increase in the number of clinical applications. Multiple characteristics of single cells can be analyzed rapidly by flow cytometry. Both qualitative and quantitative information are obtained by flow cytometry whereas previously only in research institutions and esteemed academic centres flow cytometers were found. With advances in technology now it is possible for secondary level hospitals to use this methodology. This paper reviews the selected applications of flow cytometry in the clinical haematology laboratory in Bangladesh. This review serves to awaken the interest of stakeholders involved in the diagnosis and management of haematological malignancies (HM) in the efficacy of flow cytometry in the immunophenotypic characterization of leukaemias and lymphomas. Relevant literature including those provided by different international consensus groups on the phenotypic characterization of HM was reviewed. Additionally, recent reports on the immunophenotypic analysis of HM published in haematology, oncology, pathology, immunology and cell biology journals were also analyzed. Flow cytometric immunophenotyping of HM is highly demanding. It is highly useful in profiling the leukaemias and lymphomas and allows proper ramification along the latest WHO classification guidelines, thereby paving the way for targeted therapy and clinical trial-driven management, significantly outweighs the cost, which can be fully recovered if properly managed. In a low-resource setting like Bangladesh, limited immunohistochemistry serves to bridge the gap in technological advancement. Journal of Armed Forces Medical College Bangladesh Vol.11(1) 2015: 74-80